Berakhyah Ben Natronai ha-Nakdan : Sefer ko'aḥ ha-avanim (On the virtue of the stones) ; Hebrew text and English translation ; with lexicological analysis of the romance terminology and source study - Berechiah ben Natronai, ha-Nakdan, active 12th century-13th century (Études sur le judaïsme médiéval ;, 2010)
The lore of the supposed magic and medical virtue of stones goes back to the Babylonians and peaks out in the lapidary literature of the Middle Ages. The famous work of Marbode of Rennes, which made lapidaries a very popular type of medieval scientific literature, was translated into numerous vernacular languages. The Jewish tradition, missing a particular lapidary literature of its own, absorbed non-Jewish works like that of Marbode. Several Anglo-Norman Marbode translations could be identified as the main source of the present edited Hebrew lapidary Koa? ha-Avanim, written by Berakhyah Ben N.